2022
DOI: 10.1039/d2cc02846h
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-driven PhSSPh-catalysed regioselective hydroborylation of α,β-unsaturated carbonyl compounds with NHC-boranes

Abstract: A photo-induced transition-metal-free regioselective hydroborylation of α,β-unsaturated carbonyl compounds is developed. The PhSSPh reagent was employed as the photocatalyst, and NHC-BH3 was used as the boron source. This transformation shows...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 56 publications
1
13
0
1
Order By: Relevance
“…44 During the preparation of our manuscript, the Wang group reported an elegant regioselective hydroboration of α,β-unsaturated carbonyl compounds using PhSSPh as the catalyst. 45 Although prominent, NHC-borane reacting with other electron-deficient alkenes has remained less explored. In particular, our work can be suitable for a broad electron-deficient alkene, which is timely and attractive.…”
Section: Introductionmentioning
confidence: 99%
“…44 During the preparation of our manuscript, the Wang group reported an elegant regioselective hydroboration of α,β-unsaturated carbonyl compounds using PhSSPh as the catalyst. 45 Although prominent, NHC-borane reacting with other electron-deficient alkenes has remained less explored. In particular, our work can be suitable for a broad electron-deficient alkene, which is timely and attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our experimental findings and previous literature precedents, , the most feasible mechanism was proposed in Scheme . First, thiol can react with NHC–BH 3 to produce a key intermediate I , then visible-light-irradiation-induced homolytic cleavage of intermediate I affords a thiyl radical II and an NHC-boryl radical III .…”
Section: Resultsmentioning
confidence: 99%
“…By using NHC–BH 3 as a source of boryl radical, Curran and co-workers disclosed photoinduced 1,4-hydroborylation reactions of electron-efficient aromatics such as dicyanobenzene, cyanopyridines, and dicyanothiophenes with NHC–BH 3 (Scheme c) . Very recently, our group reported a visible-light-driven diphenyl disulfide-catalyzed regioselective hydroborylation reactions of α,β-unsaturated carbonyl compounds with NHC–BH 3 ; this transformation showed a broad range of substrates and afforded a series of α-borylcarbonyl molecules in good to excellent yields (Scheme d) …”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Wang et al reported that visible light induced the regioselective hydroborylation of α , β -unsaturated carbonyl compounds with NHC-boranes, using (PhS) 2 as the photocatalyst. This system could be conducted by blue LED light irradiation, and a variety of α -borylcarbonyl compounds could be obtained in good to excellent yields (Equation (4)) [ 115 ]. …”
Section: Boron-centered Interelement Compounds In Radical Addition Re...mentioning
confidence: 99%